Developing Joyle Digital Media with Deep Learning Approach to Foster Collaboration and Communication in Primary Education - Didi Franzhardi; Indianasari; Sefina Marantika (MIMBAR PGSD Undiksha, 2026)
Elementary education remains dominated by teacher-centered approaches, limiting students’ opportunities to interact, collaborate, and develop communication skills. Therefore, interactive digital learning media are needed to support the development of twenty-first-century competencies. This study aimed to analyze learning needs and develop Joyle, a deep learning-based digital learning medium designed to foster collaboration and communication skills among primary school students. The study employed a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, and Disseminate). The participants consisted of 30 primary school students. Data were collected through observations, interviews, and documentation using observation sheets, interview guides, and documentation records as research instruments. The data were analyzed using descriptive qualitative and quantitative techniques. The findings indicate that Joyle was successfully developed by integrating teacher and student login features, flexible instructional materials, and interactive collaboration and communication menus. The implementation of the media enhanced students' engagement in learning activities, promoted more effective peer communication, and created a more collaborative and enjoyable learning environment. This study concludes that Joyle, developed based on a deep learning approach, is a valid and practical digital learning medium for strengthening students' collaboration and communication skills. The findings imply that integrating deep learning-based digital media into classroom instruction offers an innovative alternative for supporting the implementation of the Merdeka Curriculum while fostering the development of essential twenty-first-century competencies in primary education.